Flexible composite scintillation film and preparation method thereof

By combining rare earth sulfide oxide powder and optical glue, a flexible composite scintillation film is prepared, which solves the problems of high cost and structural rigidity of traditional scintillation materials, achieves flexibility and high luminous efficiency, and effectively solves the problem of digital flat panel detectors. The problem of cone beam artifacts in imaging.

CN119351098APending Publication Date: 2025-01-24NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411261671.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The manufacturing process of traditional scintillation materials requires high crystallization temperature and long processing time, resulting in high costs. At the same time, the inherent structural rigidity of these materials limits their potential to form special structures and cannot effectively solve the problem of cone beam artifacts in digital flat panel detector imaging. .

Method used

The rare earth sulfur oxide powder is compounded with optical glue, and the flexible composite flashing film is prepared through step milling, vacuum exhaust treatment, coating and curing, etc., to achieve the flexibility and high hair light efficiency of the material.

Benefits of technology

It reduces the manufacturing cost of scintillation materials, can prepare detector elements with complex curved surfaces according to the surface shape of the tested sample, solves the problem of X-ray cone beam artifacts, and improves the performance and quality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351098A_ABST
    Figure CN119351098A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a flexible composite scintillation film. The preparation method specifically comprises the following steps: S1, uniformly mixing rare earth sulfur oxide powder, optical cement, a dispersing agent and a curing agent through ball milling treatment to obtain homogeneous slurry; s2, in a vacuum environment, performing exhaust treatment on the homogeneous slurry prepared in the step S1 to obtain degassed slurry; s3, uniformly coating a substrate with the degassed slurry prepared in the step S2 to obtain a thin film; and S4, curing the film prepared in the step S3 to obtain the flexible composite scintillation film. Compared with the prior art, the preparation method of the rare earth oxysulfide flexible composite scintillation film provided by the invention has the advantages that the excellent flexibility and machinability of the film are utilized, and the preparation of scintillator detectors in any shape can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sulfur oxide scintillating materials, and in particular to a flexible composite scintillating film and a preparation method thereof. Background Art

[0002] Scintillators are a class of materials that can convert high-energy radiation or particles, such as X-rays and neutrons, into ultraviolet or visible light through scintillation. These materials have been widely used in various fields, including high-energy physics experiments, medical diagnosis, radiation detection and other related fields. Traditionally, crystal and ceramic scintillators such as CsI, BGO, (Lu,Y)2SiO5(LYSO), Gd2O2S:Pr and Gd3(Al,Ga)5O 12 have been widely used. However, the manufacturing process of these traditional scintillating materials requires high crystallization temperatures and long processing times, which leads to the high cost of these materials. In addition, the inherent structural rigidity of these materials limits their potential to form special structures, such as slender scintillating fibers or curved detectors. In particular, in digital flat-panel detector imaging applications, due to the conical nature of the X-ray beam in computed tomography data acquisition, only the center line beam is perpendicular to the detector plane, and the area outside the center position is inclined at a certain angle to the plane, which hinders the accurate display of the lesion and causes the generation of artifacts, that is, the cone beam artifact problem. If the scintillator detector is flexible and can be assembled into an arc shape, so that X-rays incident at different angles can be perpendicular to the detector plane, the problem of cone beam artifacts can be solved.

[0003] Organic-inorganic composite scintillator films, which are made of inorganic scintillators and organic polymer matrices, combine the high scintillation efficiency of inorganic scintillators and the high flexibility of polymers, and can effectively solve the problem of cone beam artifacts in digital flat-panel detector imaging applications. In the design and optimization of composite scintillator materials, the characteristics of inorganic components (such as atomic number, decay time and scintillation efficiency) become key factors in improving performance. In particular, rare earth sulfur oxides (Re 1-x , Re' x)2 O2S), with its excellent properties such as high density, fast decay and low afterglow, as an inorganic component of the composite material, can significantly improve the scintillation efficiency and show great application prospects in the field of X-ray imaging. Summary of the invention

[0004] In order to solve the above-mentioned technical problems, the present invention provides a rare earth oxysulfide flexible composite scintillating film and a preparation method thereof. The prepared rare earth oxysulfide flexible composite scintillating film has excellent flexibility, processability and high luminous efficiency.

[0005] The present invention provides a method for preparing a flexible composite scintillating film, the method specifically comprising the following steps:

[0006] S1. Uniformly mix rare earth sulfur oxide powder, optical glue, dispersant and curing agent through ball milling treatment to obtain a homogeneous slurry;

[0007] S2. In a vacuum environment, perform degassing treatment on the homogeneous slurry prepared in step S1 to obtain a degassed slurry;

[0008] S3. Uniformly coat the degassed slurry prepared in step S2 on a substrate to obtain a thin film;

[0009] S4. Cure the thin film prepared in step S3 to obtain a flexible composite scintillation film.

[0010] Compared with the prior art, in the present invention, by compounding rare earth sulfur oxide powder with optical glue and curing to form a composite scintillation film with good flexibility and processability, not only can the manufacturing cost of the scintillation material be greatly reduced, but also detector elements with complex curved surfaces can be prepared according to the surface shape of the sample to be measured, providing an effective way for X-ray imaging of irregularly shaped complex objects or solving the problem of X-ray cone beam artifacts.

[0011] In some embodiments, in step S1, the general formula of the rare earth sulfur oxide in the rare earth sulfur oxide powder is (Re 1-x , Re’ x )2O2S, where Re is used as the matrix atom, Re’ is used as the luminescent ion, Re is selected from at least one of the rare earth elements La, Gd, Y, and Lu, Re’ is selected from at least one of Pr, Tb, and Eu, and 0 < x ≤ 0.2.

[0012] In some embodiments, the particle size R of the rare earth sulfur oxide powder is: 0.01 μm < R ≤ 100 μm, and the rare earth sulfur oxide powder has a complete grain structure.

[0013] Compared with the prior art, in the present invention, by controlling the particle size of the rare earth sulfur oxide powder, the slurry stability and the fluorescence efficiency of the thin film can be satisfied at the same time, further improving the performance and quality of the overall material; in addition, the developed complete grain structure can make the grains show a low degree of mutual connection, thereby improving the high purity and excellent dispersibility of the powder.

[0014] In some embodiments, in step S1, by mass percentage, the mass ratio of the rare earth sulfur oxide powder is 10 - 50 wt.%, the mass ratio of the dispersant is 0.1 - 3.0 wt.%, the mass ratio of the optical glue is 40 - 90 wt.%, and the mass ratio of the curing agent is 4 - 9 wt%.

[0015] In some embodiments, in step S1, the dispersant is selected from at least one of polyacrylate, polyvinyl pyrrolidone, polyethylene glycol and polyacrylamide, and the optical adhesive is selected from at least one of polymethyl methacrylate, polydimethylsiloxane and epoxy resin.

[0016] In some embodiments, in step S1, the specific steps of ball milling are as follows: adding the dispersant, optical glue and zirconium oxide balls into a ball mill together, closing the cover of the ball mill and starting a planetary mixer, allowing the dispersant to be fully dissolved in the optical glue under preliminary stirring, and then adding rare earth sulfur oxide powder and curing agent into the ball mill, continuing to ball mill on the planetary ball mill, setting the speed of the ball mill to 400r / min, and obtaining a homogeneous slurry after ball milling for 1h.

[0017] In some embodiments, in step S2, a stirring process is performed simultaneously with the exhaust process, and the stirring process is performed by magnetic stirring or mechanical stirring.

[0018] In some embodiments, in step S3, the coating method is selected from one of blade coating, casting and spin coating.

[0019] In some embodiments, in step S3, the thickness of the film is controlled to be 0.01-5 mm by controlling the gap between the scraper and the cast film.

[0020] Compared with the prior art, the present invention limits the thickness of the film within the above range, which can simultaneously maintain the integrity and good flexibility of the film.

[0021] In some embodiments, in step S4, the curing process is performed in an oven, and the parameters of the curing process are as follows: temperature is 0-180° C., and time is 1-10 h.

[0022] Compared with the prior art, the present invention can cross-link the optical adhesive molecules to form a solid film by controlling the curing temperature and time, and evenly wrap the rare earth oxysulfide powder inside.

[0023] The second object of the present invention is to provide a flexible composite scintillating film, which is prepared by the above preparation method.

[0024] Compared with the prior art, the method for preparing a rare earth oxysulfide flexible composite scintillating film provided by the present invention can realize the preparation of scintillator detectors of arbitrary shapes by utilizing the excellent flexibility and processability of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a cutting and curling display diagram of the Gd2O2S:Pr-PDMS film prepared in Example 1;

[0026] Figure 2 Actual photos of Gd2O2S:Pr-ER films of different thicknesses prepared in Example 2;

[0027] Figure 3 This is a diagram showing the imaging effect of Gd2O2S:Pr-ER films of different thicknesses prepared in Example 2 on the chip structure;

[0028] Figure 4 This is the line imaging resolution diagram of Gd2O2S:Pr-ER films of different thicknesses prepared in Example 2. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0030] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0031] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0032] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0033] It is worth mentioning that the curing agent used in this embodiment is a common curing agent available on the market.

[0034] Example 1

[0035] This embodiment provides a rare earth sulfur oxide composite scintillating film, the chemical composition of which is (Gd 0.999 ,Pr 0.001 )2O2S, which is prepared by the following method:

[0036] S1. Powder preparation: 47.8344 g of gadolinium oxide, 0.0450 g of praseodymium oxide, 16.8905 g of sulfur powder, 0.5 g of sodium carbonate, 200 g of zirconium oxide grinding balls, and 13 mL of anhydrous ethanol were weighed separately and added into a ball mill, and then mixed evenly using a planetary ball mill at a speed of 80 r / min for 11 h. After ball milling, the slurry was separated from the grinding balls and dried in an oven at 80°C for 10 h to ensure complete drying. After the powder is completely dried, it is ground with a mortar and passed through a 200-mesh sieve; the sieved powder is then placed in an alumina crucible and placed in a corundum tube furnace for calcination at a temperature of 1150°C for 4 hours; after the powder is calcined and cooled, it is ground with a mortar again and passed through a 200-mesh sieve; in order to remove a small amount of unreacted oxide raw materials and impurities that may remain in the powder, the sieved powder is acid-washed; then, it is washed with deionized water for multiple times until the washing liquid is neutral; finally, the washed powder is placed in an oven to dry until the water is completely removed, thereby obtaining high-purity (Gd 0.999 ,Pr 0.001 )2O2S powder, the powder has a complete grain structure, and the particle size range of the powder is 0.01μm <R≤100μm;

[0037] S2. Preparation of slurry: Weigh 1.5 g polyvinyl pyrrolidone, 200 g zirconium oxide balls, and 120 g PDMS (molecular weight: ~25000) component, and add them into a ball mill; close the ball mill cover, start the planetary ball mill, and fully dissolve the polyvinyl pyrrolidone in the PDMS. This process is accompanied by the initial stirring of the ball mill; after the polyvinyl pyrrolidone is dissolved, weigh 50 g (Gd 0.999 ,Pr 0.001 )2O2S (Gd2O2S) powder and 12g of curing agent are added to a ball mill and continue to be ball milled on a planetary ball mill at a speed of 400 rpm for 1 hour to form a slurry with the required properties; then the slurry is poured out and placed in a vacuum box for 1 minute to remove bubbles, and the degassing process is accompanied by magnetic stirring to prevent powder sedimentation;

[0038] S3, tape casting: pour the prepared slurry into the material tank of the tape casting machine, start the tape casting machine, make the slurry move with the cast film to form a film of uniform thickness, and control the thickness of the film by controlling the gap between the scraper and the cast film;

[0039] S4. Curing: placing the tape-cast film in an oven at 65° C. for 4 hours to promote the formation of the Gd2O2S-PDMS composite film.

[0040] like Figure 1As shown, the Gd2O2S-PDMS composite film after curing in this embodiment has excellent flexibility and can be cut and bent arbitrarily.

[0041] Example 2

[0042] This embodiment provides a rare earth sulfur oxide composite scintillating film, the chemical composition of which is (Gd 0.999 ,Pr 0.001 )2O2S, which is prepared by the following method:

[0043] S1. Powder preparation: 47.8344 g of gadolinium oxide, 0.0450 g of praseodymium oxide, 16.8905 g of sulfur powder, 0.5 g of sodium carbonate, 200 g of zirconium oxide grinding balls, and 13 mL of anhydrous ethanol were weighed separately and added into a ball mill, and then mixed evenly using a planetary ball mill at a speed of 80 r / min for 11 h. After ball milling, the slurry was separated from the grinding balls and dried in an oven at 80°C for 10 h to ensure complete drying. After the powder is completely dried, it is ground with a mortar and passed through a 200-mesh sieve; the sieved powder is then placed in an alumina crucible and placed in a corundum tube furnace for calcination at a temperature of 1150°C for 4 hours; after the powder is calcined and cooled, it is ground with a mortar again and passed through a 200-mesh sieve; in order to remove a small amount of unreacted oxide raw materials and impurities that may remain in the powder, the sieved powder is acid-washed; then, it is washed with deionized water for multiple times until the washing liquid is neutral; finally, the washed powder is placed in an oven to dry until the water is completely removed, thereby obtaining high-purity (Gd 0.999 ,Pr 0.001 )2O2S powder, the powder has a complete grain structure, and the particle size range of the powder is 0.01μm <R≤100μm;

[0044] S2. Preparation of slurry: Weigh 1.5 g polyvinyl pyrrolidone, 200 g zirconium oxide balls, and 75 g epoxy resin (ER) components, and add them into a ball mill; close the cover of the ball mill, start the planetary ball mill, and fully dissolve the polyvinyl pyrrolidone in the ER. This process is accompanied by the initial stirring of the ball mill; after the polyvinyl pyrrolidone is dissolved, weigh 50 g (Gd 0.999 ,Pr 0.001 )2O2S (Gd2O2S) powder and 25g of curing agent are added to a ball mill and continue to be ball milled on a planetary ball mill at a speed of 400 rpm for 1 hour to form a slurry with the required properties; then the slurry is poured out and placed in a vacuum box for 1 minute to remove bubbles, and the degassing process is accompanied by magnetic stirring to prevent powder sedimentation;

[0045] S3, tape casting: pour the prepared slurry into the material tank of the tape casting machine, start the tape casting machine, make the slurry move with the cast film to form a film of uniform thickness, and obtain films of different thicknesses by controlling the gap between the scraper and the cast film;

[0046] S4, curing: placing the films of different thicknesses tape-cast in step S3 in an oven at 65° C. for 4 hours to promote the formation of the Gd2O2S-ER composite film.

[0047] The Gd2O2S-ER composite film of this embodiment has good flexibility after curing, and the thicknesses are 500 μm, 200 μm and 100 μm respectively. The flexibility of the above three composite scintillating films with different thicknesses is as follows: Figure 2 ,from Figure 2 It can be seen that as the thickness decreases, the flexibility of the composite scintillating film improves.

[0048] Performance Testing

[0049] X-ray imaging: The composite scintillating films with thicknesses of 500 μm, 200 μm and 100 μm prepared in Example 2 were used for chip imaging. The results are as follows: Figure 3 As shown, a1 is the imaging effect of a 500 μm-thick film on the chip structure, a2 is the imaging effect of a 200 μm-thick film on the chip structure, and a3 is the imaging effect of a 100 μm-thick film on the chip structure; Figure 3 It can be seen that under X-ray excitation (tube voltage, current and exposure time are set to 20 kV, 200 μA and 6 s respectively), the circuit information inside the chip can be clearly seen, and as the film thickness decreases, the image clarity will also increase.

[0050] Imaging resolution test: To quantify the impact of composite scintillating film on imaging quality, the chip was replaced with a line pair card. The results are as follows: Figure 4 As shown, b1 is the line imaging resolution of a thin film with a thickness of 500 μm, b2 is the line imaging resolution of a thin film with a thickness of 200 μm, and b3 is the line imaging resolution of a thin film with a thickness of 100 μm. Figure 4 From the results of X-ray irradiation of the composite scintillating film, it can be seen that when the thickness of the composite scintillating film is 500μm, 200μm and 100μm, the resolution of the composite film is 4.5LP / mm, 6LP / mm and 8LP / mm respectively.

[0051] Example 3

[0052] This embodiment provides a rare earth sulfur oxide composite scintillating film, the chemical composition of which is (Gd 0.999 ,Pr 0.001)2O2S, the only difference from Example 2 is that the dispersant in this example is obtained by mixing 0.8g of polyacrylate and 0.7g of polyacrylamide, and the rest is the same as Example 2 and will not be repeated here.

[0053] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a flexible composite scintillating film, characterized in that: The preparation method specifically includes the following steps: S1. Uniformly mix rare earth sulfur oxide powder, optical glue, dispersant and curing agent through ball milling treatment to obtain a homogeneous slurry; S2. In a vacuum environment, perform degassing treatment on the homogeneous slurry obtained in step S1 to obtain a degassed slurry; S3. Uniformly coat the degassed slurry obtained in step S2 on a substrate to obtain a thin film; S4. Subject the thin film obtained in step S3 to curing treatment to obtain a flexible composite scintillation thin film.

2. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S1, the general formula of the rare earth sulfur oxide in the rare earth sulfur oxide powder is (Re 1-x ,Re' x )2O2S, wherein Re is used as a matrix atom, Re' is used as a luminescent ion, Re is selected from at least one of the rare earth elements La, Gd, Y and Lu, and Re' is selected from at least one of Pr, Tb and Eu, 0 <x≤0.2。 3. The method for preparing the flexible composite scintillating film according to claim 2, characterized in that: The particle size R of the rare earth sulfur oxide powder is: 0.01 μm < R ≤ 100 μm, and the rare earth sulfur oxide powder has a complete crystal grain structure.

4. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S1, by mass percentage, the mass ratio of the rare earth sulfur oxide powder is 10 - 50 wt.%, the mass ratio of the dispersant is 0.1 - 3.0 wt.%, the mass ratio of the optical glue is 40 - 90 wt.%, and the mass ratio of the curing agent is 4 - 9 wt%.

5. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S1, the dispersant is selected from at least one of polyacrylate, polyvinylpyrrolidone, polyethylene glycol and polyacrylamide, and the optical glue is selected from at least one of polymethyl methacrylate, polydimethylsiloxane and epoxy resin.

6. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S1, the specific steps of the ball milling treatment are as follows: Add the dispersant, optical glue and zirconia balls into the ball milling tank together. After closing the lid of the ball milling tank, start the planetary mixer. Under the preliminary stirring effect, make the dispersant fully dissolve in the optical glue, and then add the rare earth sulfur oxide powder and the curing agent into the ball milling tank. Continue to ball mill on the planetary ball mill, set the rotation speed of the ball mill to 400 r / min, and obtain a homogeneous slurry after ball milling for 1 h.

7. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S2, stirring treatment is also performed while performing the degassing treatment, and the method of the stirring treatment is magnetic stirring or mechanical stirring.

8. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S3, the coating method is selected from one of the doctor blade method, casting method and spin coating method; And / or, in step S3, the thickness of the thin film is controlled to be 0.01 - 5 mm by controlling the gap between the doctor blade and the casting film.

9. The method for preparing the flexible composite scintillating film according to claim 1, characterized in that: In step S4, the curing treatment is carried out in an oven, and the parameters of the curing treatment are as follows: the temperature is 0 - 180 °C, and the time is 1 - 10 h.

10. A flexible composite scintillating film, characterized in that: Prepared by using the preparation method described in any one of claims 1 - 9.

Citation Information

Cited By

  • Preparation method and imaging application of dot matrix distribution flexible scintillation film

    CN122410585A